A comparative study on nanoinclusion effect of MoS2 nanosheets and MoS2 quantum dots on fracture toughness and interfacial properties of epoxy composites. (July 2021) - Riaz, Shahina; Park, Soo-Jin
Highlights: MoS2 powder was exfoliated into MoS2 nanosheets (MNSs) and quantum dots (MQDs). Nanoinclusion effect of MNSs and MQDs on the fracture toughness and interfacial properties of epoxy (EP) composites has been compared. The fracture toughness of EP composites increased by 81% and 68% after adding MQDs and MNS in the EP matrix, respectively. The surface free energy of EP composites increased by 21% and 15% after adding MQDs and MNS in the EP matrix, respectively. Abstract: Although the reinforcement effect of molybdenum sulfide (MoS2 ) nanosheets (MNSs) on the mechanical properties of epoxy (EP) composites has been extensively studied. However, the effect of MoS2 quantum dots (MQDs) on the mechanical properties of EP composites and comparing them with MNSs has not yet been reported. In this study, we exfoliated bulk MoS2 into MNSs and MQDs and used them as reinforcement materials to fabricate a series of high-performance EP composites. The results demonstrate that MQDs remarkably enhanced the fracture toughness (55–81%), flexural strength (25–66%), modulus (0.7–6%), impact strength (31–118%), and interfacial interactions (surface free energies: 1–21%) compared to neat EP and reinforcement with MNSs at the same additive amount. The superior performance of the EMQD composites over their EMNS counterparts can be attributed to the smaller size (<5 nm) and dimensions of the MQDs that resulted in their excellent dispersion and better interfacial interactions with the EP matrix, enabling them to successfully fill the free volume and cavities that resulted in improved mechanical and interfacial properties. We believe that MQDs are the starting point for new and more sophisticated multifunctional composites with a wide variety of polymer resins.